(untitled) (Journal of Educational Sciences, 2016)
The forming of a competent model of bachelor in the university is considered on basis of ISO 9000-2000 standards. It is shown that the process of permanent improvement is recommended to introduce for the improvement of educational activities. It is noted that the arrangement of educational process should be founded on the principle of continuity and consistency. Described the joint productive activity teachers and students to implement mezhsubektnyh interactions. Shows the fundamental role of bachelor for the formation of professional activity. Emphasized the need for the presence of species and forms of the student’s performance, adequate future vocational and educational work. The relevance of the use of ICT for the modernization of the educational process.